Potential effective treatment of shortening continuous erythropoietin receptor activator treatment interval combined with iron supplementation in hemodialysis patients - Yuki Kawai (Journal of Pharmacological Sciences, 2021)
Our previous randomized controlled trial comparing the total dose of weekly versus biweekly continuous erythropoietin receptor activator (CERA) therapy to maintain optimal hemoglobin (Hb) levels showed no significant differences between the two therapies. This post-hoc analysis assessed whether the total dose of weekly versus biweekly CERA therapy to maintain Hb levels among HD patients differed among groups with or without iron supplementation. Of 107 patients, 40 received intravenous iron supplementation due to iron deficiency (iron group) and 67 did not (non-iron group). In the iron group, the weekly therapy tended to require a lower total CERA dose compared with the biweekly therapy (274 ± 274 vs 381 ± 223 μg/12 weeks, P = 0.051). Changes in circulating hepcidin levels, a negative regulator of intestinal iron uptake, after 2 weeks of CERA treatment were significantly lower in the weekly therapy compared with the biweekly therapy (−4.2 ± 6.3 vs 11.1 ± 7.3 ng/mL, P = 0.015). In the non-iron group, there were no significant differences in total CERA dose or changes in hepcidin levels between the two therapies. Shortening the CERA treatment interval combined with iron supplementation may lead to the more efficient treatment of HD patients with iron deficiency.